2017
DOI: 10.1523/eneuro.0324-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Gustatory System in the Coordination of Feeding

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…Insects have a complex gustatory system and consists of different body appendages e.g ., mouthparts, legs, palps and wings ( Amrein & Thorne, 2005 ; Stocker, 1994 ; Thoma, Kobayashi & Tanimoto, 2017 ; Yosano et al, 2020 ). Feeding ethogram of insects has a specialized sequence for acceptance and intake of food ( Thoma et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insects have a complex gustatory system and consists of different body appendages e.g ., mouthparts, legs, palps and wings ( Amrein & Thorne, 2005 ; Stocker, 1994 ; Thoma, Kobayashi & Tanimoto, 2017 ; Yosano et al, 2020 ). Feeding ethogram of insects has a specialized sequence for acceptance and intake of food ( Thoma et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…When hungry insects come across food, then immediately stop their movement of body appendages and performed the following behaviors. First, insects must decide if food is acceptable or not; second, indeed they have a systematic feeding sequence, and third, locomotion of body appendages slow and stop so that they can only focus on feeding ( Dethier & Elizabeth, 1977 ; Joseph & Carlson, 2015 ; Thoma, Kobayashi & Tanimoto, 2017 ). Feeding sequence explains the main role of antennae, mouthparts, legs and ovipositor in gustatory taste ( Araya & Padilla, 2020 ; Thoma, Kobayashi & Tanimoto, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Seeds et al have shown this beautifully on the example of grooming behavior (Seeds et al, 2014). Multiple studies have analyzed the neuronal mechanisms underlying attraction to food and food seeking, food finding, and feeding itself in Drosophila and other animals (Thoma et al, 2017). Nevertheless, how these behaviors that are typically mutually exclusive and consecutive, relate and regulate each other is not well understood as prior work has focused primarily on long-term effects of hunger and feeding (Pool and Scott, 2014;Su and Wang, 2014).…”
Section: Food Search and Feeding -Sequential And Antagonistic Behaviorsmentioning
confidence: 99%
“…Satiety counteracts the drive to find food, but a too small or not palatable food source should quickly re-induce food search, as it can be considered a reward prediction error. Similarly, feeding itself represents a series of consecutive behaviors that are, in part, mutually exclusive, and suppress or are suppressed by locomotion (Mann et al, 2013;Thoma et al, 2016;Thoma et al, 2017). Moreover, ingestion is regulated by feeding through a group of cholinergic interneurons that receive pharyngeal taste information (i.e.…”
Section: Food Search and Feeding -Sequential And Antagonistic Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation